Single-Molecule Fluorescence Spectroscopy of the Folding of a Repeat Protein - Cohen, Sharona; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
In this thesis single-molecule fluorescence resonance energy transfer (FRET) spectroscopy was used to study the folding of a protein that belongs to the large and important family of repeat proteins. Cohen shows that the dynamics of the expanded conformations is likely to be very fast, suggesting a spring-like motion of the whole chain. The findings shed new light on the elasticity of structure in repeat proteins, which is related to their function in binding multiple and disparate partners. This concise research summary provides useful insights for students beginning a PhD in this or a related area, and researchers entering this field.
Abstract -- Introduction -- Methods -- Results -- Discussion -- Summary and Future Plans.
Keywords: Bioorganic chemistry; Spectrum analysis; Biophysics; Bioorganic Chemistry; Spectroscopy; Biophysics